On Generalized Weyl Fractional q-Integral Operator of General Class of q-Polynomials - Shimelis, Biniyam; Suthar, D.L. (Discontinuity, Nonlinearity, and Complexity, 2026)
In the present paper, we obtain generalized Weyl fractional q-integrals of the general class of q-polynomials and demonstrate their use by studying q-Konhouser biorthogonal polynomial, q-Jacobi polynomials and basic analogue of the Kampé de Fériet function. Polynomials have been obtained as a particular case of our major findings.